Research on Meshing Efficiency of Gear Pairs Based on Dynamic Sliding Friction Factors - Fu Jingbo; Qiao Mingming; Guo Zhili; Chen Jiangyi (Jixie chuandong)
In order to study the meshing efficiency of the gear pair under the actual working conditions, the force and kinematics of the contact surface of the gear pair are analyzed, the lubrication state of the gear pair is judged by combining the theory of elastohydrodynamic lubrication, and the relationship between the elastohydrodynamic lubrication and the mixed lubrication state is established. The mathematical model of the dynamic friction factor is used to obtain the friction factor of the gear pair at different meshing positions along the meshing line. From the point of view of force, the calculation formula of gear pair meshing efficiency is deduced, and the dynamic sliding friction factor is introduced to obtain the result of gear pair meshing efficiency that conforms to the actual working conditions. Combined with the simulation analysis software, the influence of the transmission ratio and the number of pinion teeth on the sliding friction factor and the meshing efficiency of the gear pair is analyzed. The results show that the calculation method of the gear pair meshing efficiency based on dynamic sliding friction factor is in good agreement with the actual working conditions, which has certain guiding significance for gear transmission design.